Severe acute respiratory syndrome coronavirus-2-associated cholangiopathies. Issue 2 (22nd March 2022) - Bartoli, Alessandra; Cursaro, Carmela; Andreone, Pietro
Abstract : Purpose of review: SARS-CoV2 is a β-coronavirus, isolated for the first time in Wuhan in December 2019. Bilateral interstitial pneumonia is the hallmark of this disease. Liver is the second viral target for frequency and AST and ALT elevation is a common finding. From February 2020, two different cholangiopathies have been reported in COVID-19 patients. The aim of this article is to review the cases so far described in order to share information and awareness about these new clinical entities. Recent findings: SARS-CoV2 seems to trigger autoimmunity and two cases of primary biliary cholangitis (PBC) have been developed after viral infection while more than 30 patients have showed a rapidly progressing cholangiopathy with features of secondary sclerosing cholangitis (SSC). For what concerns SSC pathogenesis, a theory combining multiple hits is the most recognized. Summary: Two different cholangiopathies have been reported in patients after severe-COVID-19. Attention should be paid to the development of cholestasis in ICU setting but above all after discharge and liver function tests should be, therefore, periodically performed. No treatment strategies are available and liver transplantation remains the last option in individuals with liver failure because of SSC. Other efforts are necessary to better understand the pathogenesis and to expand therapeutic options.